Leak detection systems in oil and gas fields: Present trends and future prospects. (October 2020) - Meribout, Mahmoud; Khezzar, Lyes; Azzi, Abdelwahid; Ghendour, Nabil
Abstract: Early leak detection of liquid and gas of both buried and unburied pipelines remain a critical task for economical and safety reasons. Several techniques were recently suggested and tested in real-life conditions and the corresponding results are very encouraging since they offer low cost solution while they yield both true detection and accurate localization of the leak. However, most of the techniques are not robust enough for all possible scenarios and may fail under certain environmental conditions. This review paper presents the most recent findings in acoustic and infrared (IR)-based leak detection techniques which remain the most widely used techniques for liquid and gas leaks detections respectively. However, they may fail under some situations. For instance IR-based techniques are not adequate during rainy, humid, or sandy weather or when ppb sensitivity is required, while acoustic sensors are not adequate for gas leak detection or when additional sources of acoustic noise are in the vicinity of the target area. Thus, the paper provides other alternative techniques such as ground penetrating radar (GPR), temperature profiling, and photoacoustic sensing techniques. Several important research works and real-life applications are cited in an attempt to provide a reasonable cross-section of various techniques. The paper can be useful for either a fresh researcher in the area, or for a skilled R&D engineer involved in the design of a leak detection solution since it presents the most recent leak detection techniques. Highlights: Acoustic-based leak detection. IR-based leak detection. GPR-based leak detection.